Qualitative Research Methods: A Critical Analysis - Willy Lima, MBA; Prof. Enid F. Newell-McLymont (International Journal of Engineering and Management Research, 2021)
Creswell (2014) noted that qualitative research is an approach for exploring and understanding the meaning individuals or groups ascribe to a social or human problem. The article embodies a critical analysis of chapters one to twelve of Stake (2010). In chapter one, Qualitative research: How things work is seen as qualitative, is based on a comprehensive aim seeking to answer the questions why and how. It analyzes actions and interactions, taking into account the intentions of the actors. An analytic perspective on the interpretation of the Person as an instrument is the thrust of chapter two. Chapter three examines the experiential understanding: Most qualitative study is experiential, in this chapter stake (2010) discusses two common research approaches, qualitative and quantitative methods. Chapter four Stating the Problem: Questioning How This Thing Works. Chapter five deals with the Methods-Gatherings Data, while chapter six illuminates the Review of Literature: Zooming to See the Problem. In chapter seven, the author implores the evidence: Bolstering Judgment and Reconnoitering. Chapter eight propels Analysis and Synthesis: How Things Work. Chapter nine acts as a mirror that invites the researcher to examine their action research and Self-Evaluation: Finding our Own How our Place Works. Finally, in chapters ten to twelve, the author compels Storytelling: Illustrating How Things Work, Writing the Final Report: An Iterative Convergence, and Advocacy and Ethics: Making Things Work Better. This work is expected to guide future researchers in developing their research in qualitative research.